Serum prolactin level as a predictive factor for abiraterone response in patients with metastatic castration‐resistant prostate cancer. Issue 13 (23rd June 2022) - Yang, Tao; Liu, Ying; Chen, Shuzhen; Tian, Jiale; Zhu, Xuyou; Zhang, Long; Wang, Wei; Qin, Yingyi; Richter, Jens; Anand, Aseem; Xu, Chengdang; Chi, Yongnan; et al.
Abstract: Background: To investigate the prognostic value and potential therapeutic target of the baseline serum hormones in patients with metastatic castration‐resistant prostate cancer (mCRPC) treated with abiraterone. Methods: This retrospective study was performed in patients with mCRPC receiving abiraterone acetate (AA) from July 2016 to September 2020. Patients who had serum hormone tests within 2 weeks before AA treatment were included. Univariate analysis and Cox regression were performed to evaluate the correlation of sex hormones with progression‐free survival (PFS) and overall survival (OS). Prolactin (PRL) expression in the clinical specimens was evaluated by immunohistochemistry. Bone metastases were quantified by automated Bone Scan Index (aBSI). Results: The study included 61 patients with a median follow‐up of 19.0 months. Patients with lower baseline PRL levels (median) responded better to AA than those with higher baseline PRL levels as indicated by prostate‐specific antigen (PSA) reduction (PSA90, 66.7% vs. 25.8%, p  = 0.001), PFS (19.6 vs. 7.9 months), and OS (52.8 vs. 19.2 months). Cox regression adjusted for clinical factors also confirmed that baseline PRL level was an independent predictive factor for PFS (hazard ratio = 1.096, p  = 0.007). Prostatic PRL expression increased as the disease progressed. PRL expression was also detected in biopsy samples from bone metastasis but not in normal bone tissue, and the serum PRL levels were positively correlated with aBSIs ( r  = 0.28, p  = 0.037). Conclusions: Serum PRL levels are predictive of response to AA in patients with mCRPC. Serum PRL levels are positively correlated with the volume of metastatic bone disease.